Prospects of the Projective Drawings Method in a Sociological Research - Otrishchenko, Natalia (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
This article is devoted to specifics and potential using of the projective drawings in the sociological researches. Particular procedures and characteristics of material obtained by applying of the method are analyzed. Author specifies difference from data obtained through traditional sociological methods. Several examples of application of the method in particular researches are evaluated. Also this article presents the possibilities of method of projective drawing, recommendations of its usage combined with the in-depth semi-structured interviews, and the ways of data interpretation. As an example, author uses the study of Lviv residents perception of their district (Pidzamche), conducted by the Center for Urban History of East Central Europe. Conclusions of this article added to the debate about the place of projective methods in general and drawing techniques particularly in the contemporary social practices.